Psychosocial and metabolic function by smoking status in individuals with binge eating disorder and obesity. (February 2016) - Udo, Tomoko; White, Marney A.; Barnes, Rachel D.; Ivezaj, Valentina; Morgan, Peter; Masheb, Robin M.; Grilo, Carlos M.
Abstract: Individuals with binge eating disorder (BED) report smoking to control appetite and weight. Smoking in BED is associated with increased risk for comorbid psychiatric disorders, but its impact on psychosocial functioning and metabolic function has not been evaluated. Participants were 429 treatment-seeking adults (72.4% women; mean age 46.2 ± 11.0 years old) with BED comorbid with obesity. Participants were categorized into current smokers ( n  = 66), former smokers ( n  = 145), and never smokers ( n  = 218). Smoking status was unrelated to most historical eating/weight variables and to current eating disorder psychopathology. Smoking status was associated with psychiatric, psychosocial, and metabolic functioning. Compared with never smokers, current smokers were more likely to meet lifetime diagnostic criteria for alcohol (OR = 5.51 [95% CI = 2.46–12.33]) and substance use disorders (OR = 7.05 [95% CI = 3.37–14.72]), poorer current physical quality of life, and increased risk for metabolic syndrome (OR = 1.80 [95% CI = 0.97–3.35]) and related metabolic risks (reduced HDL, elevated total cholesterol). On the other hand, the odds of meeting criteria for lifetime psychiatric comorbidity or metabolic abnormalities were not significantly greater in former smokers, relative to never smokers. Our findings suggest the importance of promoting smoking cessation in treatment-seeking patients with BED and obesity for its potential long-term implications for psychiatric and metabolic functioning. Highlights: Examined psychosocial, and metabolic correlates of BED and obesity by smoking status History of eating/weight problems and features of eating disorders did not differ by smoking status Current smokers were at risk for alcohol and substance use disorders and metabolic abnormalities Former and never smokers were similar on psychosocial and metabolic correlates It is important to promote smoking cessation in treatment of BED and obesity